Network of good capixaba, an experience of social organization in the prevention of alcohol, tobacco and drugs - Madeira Álvares da Silva Conforti, Adriana; Pessoa Hemerly, Jefferson; Mota de Oliveira, Mayara; Kühl, André; Vidal Monteiro da Silva Couto, Cinthia; Bonamigo, Julio Cesar; Mozer de Oliveira, Deivison; Dalbó, Juliana; Moraes Mendel Soares, Douglas; Souza dos Santos, Rosane Maria (Guará Journal, 2025)
The Rede do Bem Capixaba Project aims to act as a social network promoting drug abuse prevention activities in the cities of southern Espírito Santo, in the Caparaó Capixaba region. Activities include training courses for educators and partnerships with government agencies and civil society. Based on the guiding principles of this proposal, we hope to reach, through professional education, the essential agents of social transformation—educators—and with them, children and pre-adolescents, promoting changes in which each member of the community can "take on the role of subject of search, decision, rupture, and choice, as historical transformative subjects." Rede do Bem has been operating in the region since 2012 in 11 cities, training 1,500 people on the topic of "drugs," and having 79 undergraduate students from UFES (Federal University of Espírito Santo) and several teachers as extension workers. The Network has produced four textbooks for children aged 8 to 13, which are distributed free of charge in schools in the region. Additionally, he produced 150 videos with lessons and interviews and maintains three websites. This experience demonstrated that social transformation is possible through educational initiatives that are supported by and supportive of civil society.
Keywords: drug abuse; training; prevention; capixaba network of good